Putting the onus on authority: A review of obedient behavior and why we should move on. (January 2021) - Meyer, Michelle
Abstract: The obedience to authority domain arose in psychological research between the 1950s–1960s as a combination of interest in obedience, conformity, and compliance that expanded after Milgram's shock experiments. Each of these components compared different forms of submissive behavior as a response to authority and social pressure, but over the past fifty years the domain has merged these three components and become more centered around the shock of submissive behavior than the authority that causes it. As a result, many modern investigations use inconsistent understandings of these constructs and often leave out manipulation of the second half of the paradigm – authority. If we reintroduce the distinctions for each form of submissive behavior, we can notice patterns of how each is related to differences in authority and the systemic benefits of studying the nuances of authoritative systems. Understanding the impact of power dynamics on submissive behavior and what truly separates obedience from conformity and compliance not only allows for a more dualistic approach to this discipline, but allows the authority domain to provide insight into other domains such as education, workplace behavior, and conformity to mass media.